Size reduction of gastric fundic gland polyposis by de‐escalation of acid‐suppressive therapy. Issue 1 (5th June 2022) - Kanamori, Akira; Tominaga, Keiichi; Masuyama, Hironori; Ishikawa, Mutsumi; Masuyama, Satoshi; Kondo, Masayuki; Kanazawa, Mimari; Tanaka, Takanao; Yamaura, Masamichi; Abe, Keiichiro; Watanabe, Shoko; Yamamiya, Akira; et al.
Abstract: The patient, a 73‐year‐old woman, had been taking acid‐suppressive therapy for refractory reflux esophagitis for 10 years. A potassium‐competitive acid blocker was administered to strengthen acid‐suppressive therapy for worsening symptoms of gastroesophageal reflux disease. Esophagogastroduodenoscopy showed an increase in the number and size of fundic gland polyposis (FGPs). When acid‐suppressive therapy was changed from potassium‐competitive acid blocker to proton pump inhibitor, the FGPs showed reduced size 1 year later. Furthermore, when acid‐suppressive therapy was changed from proton pump inhibitor to histamine‐2 receptor antagonist, FGPs were even smaller after 1 and 2 years. The patient, who had no flare‐up of gastroesophageal reflux disease symptoms, continues to be treated medically with histamine‐2 receptor antagonist. This case report describes changes in endoscopic findings of a patient with FGPs caused by acid‐suppressive therapy for refractory gastroesophageal reflux disease.